THE IMPACT OF MARKETING MIX ETHICAL ISSUES ON THE CONSUMER’S PURCHASE ATTITUDES - Sanjaamanal, Bolormaa; Gantulga, Urandelger (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
In recent years, both businesses and consumers have increasingly paid attention to issues related to business ethics. Business ethics not only affect the internal operations of organizations but also play a significant role in consumers’ purchasing decisions. Therefore, it is essential to study business ethics, particularly marketing ethics. The main objective of this research is to identify how the ethical aspects of the marketing mix influence consumer purchase behavior and the factors that affect it. The study involved a total of 386 consumers, and four hypotheses were tested using SPSS 27.0 for data analysis. The results show that ethical practices related to product, pricing, and promotion in the marketing mix have a positive influence on consumer purchasing behavior. However, the hypothesis that ethics related to distribution channels positively impact consumer purchase behavior was rejected according to the study findings.